2005
DOI: 10.1517/14728222.9.5.931
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sympathetic nervous system in controlling bone metabolism

Abstract: Experimental studies have generally shown that increased sympathetic nervous activity causes bone loss via an increase in bone resorption and a decrease in bone formation. Increased bone resorption is based on the stimulation of both osteoclast formation and osteoclast activity. These effects are associated with beta2-adrenergic activity towards both osteoblastic and osteoclastic cells. Decreased bone formation is based on the inhibition of osteoblastic activity through beta2-adrenergic receptors on osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 71 publications
2
39
0
1
Order By: Relevance
“…Consistent with the BMD findings, the mCT analysis (Fig. 2B) showed increased BV/TV in L 4 and in the distal femurs of KO animals (80% and 57%, respectively). An increase in Tb.N also was observed in L 4 of KO mice (35%).…”
Section: Resultssupporting
confidence: 86%
“…Consistent with the BMD findings, the mCT analysis (Fig. 2B) showed increased BV/TV in L 4 and in the distal femurs of KO animals (80% and 57%, respectively). An increase in Tb.N also was observed in L 4 of KO mice (35%).…”
Section: Resultssupporting
confidence: 86%
“…Similar observations were described for keratinocytes (Pullar et al, 2006) and airway smooth muscle cells (Hirshman et al, 2001;Hirshman et al, 2005). Although it is well known that osteoblasts express badrenergic receptors ) and that the nervous system is involved in the regulation of bone turnover (Togari et al, 2005), the activation of b-adrenoreceptors in osteoblasts has not been previously linked to alteration of the actin cytoskeleton.…”
Section: Discussionsupporting
confidence: 74%
“…The proliferation and differentiation of mononuclear preosteoclasts and the activity of the differentiated osteoclasts are controlled by numerous systemic hormones, cytokines, growth factors, and the nervous system. Recently, the sympathetic nervous system has been implicated in bone metabolism (3,6,7,19). We previously reported that the α 1B -, α 2B -, and β 2-ARs; substance P receptor (SP-R); vasoactive intestinal peptide receptor (VIP-R); and calcitonin gene-related peptide receptor (CGRP-R) are expressed in human osteoclastic cells and that a β -adrenergic agonist was able to directly stimulate bone-resorbing activity in human osteoclastlike cells (3,20).…”
Section: Introductionmentioning
confidence: 99%